Mechanistic insight into the effect of hydrothermal treatment of sewage sludge on subsequent pyrolysis: Evolution of volatile and their interaction with pyrolysis kinetic and products compositions. (1st March 2023) - Chen, Renjie; Yuan, Shijie; Wang, Xiankai; Dai, Xiaohu; Guo, Yali; Li, Chong; Wu, Haibin; Dong, Bin
Abstract: Hydrothermal treatment (HT) is an effective thermochemical pretreatment process for improving the pyrolysis behavior and quality of products. This study systematically investigated the relationship between the compositions and structures of hydrothermally treated sewage sludge (SS) (120–260 °C) and the characteristics of the subsequent pyrolysis. The results indicated that, in the solubilization and hydrolyzation stage (120–160 °C), the hydrolyzation of thermally stable polymeric substances in the SS reduced the activation energy of pyrolysis reaction and facilitated the formation of aliphatic hydrocarbons and acids/esters in the bio-oil. Moreover, the solubilization and deamination of proteinaceous substrates during HT reduced the content of nitrogen- and sulfur-containing compounds in bio-oil and non-condensable gases. In the carbonization stage (180–260 °C), the activation energy of the HT-sludge pyrolysis reaction increased with the formation of aromatic structures. Furthermore, odxygen- and nitrogen-containing aryl compounds formed from the repolymerization of soluble intermediates were converted into acids/esters and amine/amide in the primary bio-oil during pyrolysis (450 °C). With increasing pyrolysis temperature, deamination and decarboxylation of amides and acids/esters in the primary bio-oil increasingly occurred, resulting in the release of NH3 and CO2 . Graphical abstract: Image 1 Highlights: The pyrolysis behavior of sludge was identified during different hydrothermal stages. The evolution of kinetic and products compositions during pyrolysis was studied. The devolatilization of sludge was responsible for improving pyrolysis behavior. The ring condensation of soluble intermediates facilitated the release of NOX precursors.